2004
DOI: 10.1152/japplphysiol.00836.2003
|View full text |Cite
|
Sign up to set email alerts
|

Functional genomics approach to hypoxia signaling

Abstract: Mammalian cells require a constant supply of oxygen to maintain energy balance, and sustained hypoxia can result in cell death. It is therefore not surprising that sophisticated adaptive mechanisms have evolved that enhance cell survival during hypoxia. During the past few years, there have been a growing number of reports on hypoxia-induced transcription of specific genes. In this review, we describe a unique experimental approach that utilizes focused cDNA libraries coupled to microarray analyses to identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
42
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 81 publications
1
42
0
Order By: Relevance
“…Different inhibitors were used to identify the signaling pathways involved in hypoxia-induced UII expression (Seta & Millhorn 2004). Polyclonal antibodies against JNK and mAbs against phospho-JNK were obtained from Cell Signaling (Beverly, MA, USA).…”
Section: Antibodies and Reagentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Different inhibitors were used to identify the signaling pathways involved in hypoxia-induced UII expression (Seta & Millhorn 2004). Polyclonal antibodies against JNK and mAbs against phospho-JNK were obtained from Cell Signaling (Beverly, MA, USA).…”
Section: Antibodies and Reagentsmentioning
confidence: 99%
“…In response to hypoxia, the heart also generates ROS, resulting in cardiac hypertrophy and expression of fetal cardiac genes (Inamoto et al 2006, Kontaraji et al 2007, Yamashita et al 2007) through various signaling cascades (Seta & Millhorn 2004). A previous study has shown that the density of binding sites for UII in sarcolemma of the myocardium increased in rats exposed to chronic hypoxia (Zhang et al 2002).…”
mentioning
confidence: 99%
“…
Hypoxia triggers the transcription of regulatory genes that promote O 2 delivery and anaerobic metabolism, suppress major energy-requiring processes, and inhibit growth and development in animals ranging from invertebrates to mammals (14,15,40). Hypoxia also influences several human pathological processes, such as tumorigenesis and intrauterine growth restriction (IUGR).
…”
mentioning
confidence: 99%
“…This finding may be associated with the effects of hypoxia and ischemia occurring in the melanoma microenvironment (23,24). In this type of microenvironment, tumor cells can secrete certain proteins or upregulate expression of specific proteins in order to adapt to the poor conditions (25,26).…”
Section: Discussionmentioning
confidence: 99%